THE EFFECT OF THE BI RATE STANDARD ON THE BRI SHARIA MARGIN POLICY 2015-2019 - Isti Tresna Aristantia; Suci Sulastri (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2020)
This research is motivated by the absence of provisions governing the determination of financing margins, making Islamic banks in Indonesia, namely Bank Rakyat Indonesia Syariah, still use the BI Rate as one of the references in determining margins in financing. The decline in financial conditions can be seen from the net income margin in 2014, which only reached 6.04%. The method used is a descriptive correlational method. The data used is the average BI Rate per year and the 2015-2019 BRI Syariah Annual Report. Data collection techniques used document studies and literature studies with browsing data collection instruments. Data analysis used descriptive statistics, regression, correlation, partial test, and determination. The results of the research data description of the BI Rate and the financing margin income of Bank Rakyat Indonesia Syariah in 2015-2019 experienced an increase and decrease. The results of the analysis of the influence of the BI Rate on financing margin income at Bank Rakyat Indonesia Syariah in 2015-2019 obtained the regression equation: Financing Margin Income = 10.45376 + (-0.568777 x BI Rate) + e. The correlation coefficient value is -0.79 or 79%. The accepted hypothesis is Ho, which means that there is no significant positive effect between the BI Rate on financing margin income at Bank Rakyat Indonesia Syariah 2015-2019. The conclusion is that the BI Rate does not significantly affect financing margin income at Bank Rakyat Indonesia Syariah 2015-2019.